Ethical Care: Nurses' Experience of Moral Judgment in Intensive Care Units - Hamideh Yazdimoghaddam; Zohreh Mohamadzadeh Tabrizi; Roghayeh Zardosht (Kerman University of Medical Sciences, 2023)
Background: Ethical care is concerned with aspects of work that may influence nurses' ethical behavior. Intensive care units might expose nurses to moral judgment while caring. This qualitative study aimed to explain the nurses' experience of moral judgment in intensive care units.Methods: The present qualitative study was conducted using the conventional content analysis method. The participants of the study included 23 nurses working in the intensive care units (ICU, CCU, NICU) of four hospitals affiliated with Sabzevar University of Medical Sciences who were selected using purposive sampling. The data were collected through semi-structured interviews. The questions asked in the interviews included, "Would you please describe one working day of yours caring in the intensive care units?" and "While caring, did you have to hesitate to make a decision ethically? If yes, would you describe that situation?" The Data were analyzed using the qualitative content analysis method proposed by Graneheim and Lundman.Results: Data collection and analysis led to the identification of 1 theme, 6 categories, and 23 subcategories. The identified theme was "intensified tension and conflict following ethical patient care in the intensive care units" and the categories were "repeated exposure to stress in ethical patient care in the intensive care units", "ethical care originated from the nurses' beliefs", "moral judgment in care affected by the patient's clinical condition", "moral judgment as a consequence of clinical judgment", "ethical care based on organizational and legal conditions in the moral environment", and "requirements of ethical care".Conclusion: The nurses in the intensive care units deal with ethical issues and are under a lot of stress. The results of this study can help nursing authorities pay more attention to developing ethical knowledge and ethical considerations in hospitals and provide organizational support to identify the moral tensions of nurses in intensive care units.